Epidural Blood Patch Using Manometry for Sinking Skin Flap Syndrome. Issue 11 (1st June 2016) - Turner, James D.; Farmer, Justin L.; Dobson, Sean W.
Abstract : We describe here a 55-year-old male patient with a medical history significant for chronic back pain and substance abuse with cocaine who sustained a traumatic subarachnoid hemorrhage after a fall from a roof while acutely intoxicated on cocaine requiring decompressive hemicraniectomy and cranioplasty that was complicated by an epidural abscess requiring a repeat craniectomy. He was diagnosed with sinking skin flap syndrome consistent with altered mental status and a sunken skin flap with increased midline shift. Despite treatment with Trendelenburg positioning and appropriate fluid management, the patient continued to decline, and an epidural blood patch was requested for treatment. After placement of the epidural blood patch using manometry in the epidural space, the patient's neurologic status improved allowing him to ultimately receive a cranioplasty. The patient is now able to perform several of his activities of daily living and communicate effectively.